2013
DOI: 10.1016/j.gaceta.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in HIV risk behaviours among intravenous drug users in Catalonia, Spain

Abstract: This study demonstrated differences in sexual risk behaviours between male and female IDU, but failed to find gender differences in injecting risk behaviours. Apart from that, the higher prevalence of HIV among women than among men, together with a lower prevalence of HCV, provides evidence that sexual transmission of HIV is important among female IDU. Additional studies are needed to analyze in-depth these specific risk factors for women in order to develop appropriate prevention and health education programs. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
0
17
0
3
Order By: Relevance
“…In prior literature, the nature of some forms of sex exchange (e.g., sex without a condom) renders those involved and their sexual partners vulnerable to HIV, HCV, and STI acquisition. 1,4,7,16,26,28 Prior work by Wagner and colleagues has outlined distinct differences between men and women who use injection drugs; women tend to have a much less distinct divide between social, sexual and drug networks. 27 For example, women who inject drugs more commonly become involved in injection drug use through a male partner 8,27,37–39 and frequently have a steady male partner who also injects drugs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In prior literature, the nature of some forms of sex exchange (e.g., sex without a condom) renders those involved and their sexual partners vulnerable to HIV, HCV, and STI acquisition. 1,4,7,16,26,28 Prior work by Wagner and colleagues has outlined distinct differences between men and women who use injection drugs; women tend to have a much less distinct divide between social, sexual and drug networks. 27 For example, women who inject drugs more commonly become involved in injection drug use through a male partner 8,27,37–39 and frequently have a steady male partner who also injects drugs.…”
Section: Discussionmentioning
confidence: 99%
“…27 For example, women who inject drugs more commonly become involved in injection drug use through a male partner 8,27,37–39 and frequently have a steady male partner who also injects drugs. 16 Furthermore, women who inject drugs are less likely than their male counterparts to use condoms at their last sexual episode, 16 and are more likely to have sex while intoxicated. 6,31,40 The risk of HIV, HCV, and STI acquisition, therefore, may be cumulative between the various high-risk networks that women are involved in, 27 particularly if the nature of sex exchange arises out of desperate circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have shown that injection practices of women, including higher rates of equipment and syringe sharing, women using injecting equipment following their male partners and being injected by others, may put them at higher risk . In addition, women who inject drugs have been shown to have higher incidence of HIV and higher injection‐related risk behaviours …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] In addition, women who inject drugs have been shown to have higher incidence of HIV and higher injection-related risk behaviours. [13][14][15][16] HCV surveillance data generally show lower HCV detection rates among females compared to men. Viral hepatitis statistics and surveillance in 2013 in the U.S. reported 0.5 and 0.7 cases/10 000 among females and males, respectively.…”
mentioning
confidence: 99%